The VATO project: Development and validation of a dynamic transfer model of tritium in grassland ecosystem. (May 2017) - Le Dizès, S.; Aulagnier, C.; Maro, D.; Rozet, M.; Vermorel, F.; Hébert, D.; Voiseux, C.; Solier, L.; Godinot, C.; Fievet, B.; Laguionie, P.; Connan, O.; et al.
Abstract: In this paper, a dynamic compartment model with a high temporal resolution has been investigated to describe tritium transfer in grassland ecosystems exposed to atmospheric 3 H releases from nuclear facilities under normal operating or accidental conditions. TOCATTA-χ model belongs to the larger framework of the SYMBIOSE modelling and simulation platform that aims to assess the fate and transport of a wide range of radionuclides in various environmental systems. In this context, the conceptual and mathematical models of TOCATTA-χ have been designed to be relatively simple, minimizing the number of compartments and input parameters required. In the same time, the model achieves a good compromise between easy-to-use (as it is to be used in an operational mode), explicative power and predictive accuracy in various experimental conditions. In the framework of the VATO project, the model has been tested against two-year-long in situ measurements of 3 H activity concentration monitored by IRSN in air, groundwater and grass, together with meteorological parameters, on a grass field plot located 2 km downwind of the AREVA NC La Hague nuclear reprocessing plant, as was done in the past for the evaluation of transfer of 14 C in grass. By considering fast exchanges at the vegetation-air canopy interface, the model correctly reproduces the observed variability in TFWT activity concentration in grass, which evolves in accordance with spikes in atmospheric HTO activity concentration over the previous 24 h. The average OBT activity concentration in grass is also correctly reproduced. However, the model has to be improved in order to reproduce punctual high concentration of OBT activity, as observed in December 2013. The introduction of another compartment with a fast kinetic (like TFWT) - although outside the model scope - improves the predictions by increasing the correlation coefficient from 0.29 up to 0.56 when it includes this particular point. Further experimental investigation will be undertaken by IRSN and EDF next year to better evaluate (and properly model) other aspects of tritium transfer where knowledge gaps have been identified in both experimental and modelling areas. Highlights: We model 3 H transfer from the atmosphere to grassland ecosystems on an hourly basis. Model predictions agreed fairly well with the observed variability in grass TFWT. OBT predictions could be improved by the addition of a fast kinetic compartment. Future experiments are identified in the framework of the VATO project.